Designating of Processing Unit of Corn Tortilla Chips for Small Scale Industry - Kumalaningsih, Sri; Wignyanto, Wignyanto; Fitria, Fitria (Jurnal Teknologi Pertanian, 2005)
This study was aimed at finding out the best proportion of soy flour and wheat flour needs to add in the making of corn-based tortilla chips and then used it to design a small scale industry producing such chips. A Completely Randomized Design experiment was carried out employing two factors i.e. proportion of soy flour and wheat flour respectively, at 3 levels each, and was conducted in triplicates. The results showed that an addition of 0% soy flour and 4% wheat flour was considered the best in production corn-based tortilla chips. It has a product value of 0.802, a moisture content of 4.088%, 0.710% free fatty acid, and the yield of 59.37%. Based on a production capacity of 50 kg product per day which was designed for 5 years of operation, the value of total investment needed is Rp 140,990,137.00. It was found that the production cost per unit was Rp 499.00. By defining a margin of 20%, the price of the product at a retailer level is about Rp 550.00 per unit, by assuming the consumersâ price of Rp 700.00 per unit. A break even point will be achieved at a level of production of 244,137 units of 30 gram or equal to 48.85% of its capacity operation. It means that by an operation level of 6 months a year, the unit is still able to survive. The calculated pay back periods is 3.76 years and a profitability index of 1.19. Â  Keywords: Processing unit, corn tortilla chips